Солипсизм в романной поэтике Виктора Пелевина - Mateusz Jaworski (Studia Rossica Posnaniensia)
The philosophical doctrine of solipsism plays an extremely significant role in Viktor Pelevin’s works as a core idea which undergoes the process of formal modifications. In this paper this process is referred to as “reconfiguration”. The article presents different representations of solipsism in Pelevin’s novels. The analysis is preceded by a brief introduction to the philosophical roots of the doctrine.